2001
DOI: 10.1172/jci200113930
|View full text |Cite
|
Sign up to set email alerts
|

Histamine regulates cytokine production in maturing dendritic cells, resulting in altered T cell polarization

Abstract: Atopic diseases such as allergy and asthma are characterized by increases in Th2 cells and serum IgE antibodies. The binding of allergens to IgE on mast cells triggers the release of several mediators, of which histamine is the most prevalent. Here we show that histamine, together with a maturation signal, acts directly upon immature dendritic cells (iDCs), profoundly altering their T cell polarizing capacity. We demonstrate that iDCs express two active histamine receptors, H1 and H2. Histamine did not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(96 citation statements)
references
References 53 publications
11
83
0
1
Order By: Relevance
“…Histamine can stimulate IL-5 production from CD3-stimulated T cells (38) and increase airway mucus secretion (39) via H2R. Additionally, H2R has been shown to promote Th2 responses by influencing dendritic cell activity (19) and regulating T cell proliferative responses (40). Increased expression of H2R has been found in the nasal mucosa of patients with allergic rhinitis (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histamine can stimulate IL-5 production from CD3-stimulated T cells (38) and increase airway mucus secretion (39) via H2R. Additionally, H2R has been shown to promote Th2 responses by influencing dendritic cell activity (19) and regulating T cell proliferative responses (40). Increased expression of H2R has been found in the nasal mucosa of patients with allergic rhinitis (41).…”
Section: Discussionmentioning
confidence: 99%
“…Histamine has been reported to inhibit IL-12, IL-2, and IFN-γ production by cultured cells (14), while, conversely, IL-4, IL-5, IL-10, and IL-13 are upregulated (15)(16)(17)(18). Enhancement of Th2 responses by histamine in culture is likely the result of its effects on dendritic cells (19). Caron et al (20) found that polarization of T cell responses by histamine could be accounted for by an H2R-driven differentiation of immature dendritic cells toward a Th2-generating DC2 dendritic cell phenotype.…”
Section: Introductionmentioning
confidence: 97%
“…In the differentiation process of DC1 from monocytes, HR1 and HR3 act as positive stimulants that increase antigen presentation capacity, proinflammatory cytokine production and Th1 priming activity. In contrast, HR2 acts as a suppressive molecule for antigen presentation capacity, enhances IL-10 production and induces IL-10-producing T cells or Th2 cells [45,46,47]. …”
Section: Regulation Of Immune Responsementioning
confidence: 99%
“…Maturation of DCs results in loss of these responses. However, in maturing DCs, histamine dose-dependently enhances intracellular cAMP levels and stimulates IL-10 secretion, while inhibiting production of IL-12 via HR2 [46]. Interestingly, although human monocyte-derived DCs have both HR1 and HR2 and can induce CD86 expression by histamine, human epidermal Langerhans cells do not express either HR1 or HR2 [52].…”
Section: Regulation Of Immune Responsementioning
confidence: 99%
See 1 more Smart Citation